Pandemi Covid-19 dan Transformasi Pendidikan Kewirausahaan: Sebuah Studi Literatur - Erlintang Dwi Crisliyani Asholikha; Jaka Nugraha (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2021)
Covid-19 has significantly affected the education community, particularly in face-to-face learning towards online learning. This means a rapid transformation from curriculum and learning style to digital platforms. The purpose of this writing is to analyze the impact of online learning on entrepreneurial education learning conditions and analyze learning innovation and entrepreneurial education learning strategies, and analyze the application of learning methods through the Entrepreneurship Community approach before and after the Covid19 pandemic. This paper is a literature view that discusses how the entrepreneurial education practitioner community can deal with the Covid-19 pandemic. While the majority of school's entrepreneurial educators have taught online before, many are unfamiliar with the tools and applications of Educational technology, which demonstrate opportunities for sustainable professional development. As a result of the shift to online learning and teaching methods, digital disruption to education has accelerated. It presents a unique opportunity to incorporate more creativity and innovation into the educational experience, thus facilitating the transition to digital technology. Therefore, there is a great opportunity for entrepreneurial educators to use their existing expertise to gain new techniques that can enable a more contextual learning environment. It is hoped that the discussion given in this article can provide advice and assistance on how to foster entrepreneurial education experiences due to the Covid-19 crisis. This is the first study to investigate how school entrepreneurial educators respond to the Covid-19 pandemic that impacts entrepreneurship education.